Effect of immersion in sodium hypochlorite on cyclic fatigue resistance of RaCe, HyFlex CM and XP-endo shaper files - Esmaeel Dadgar; Masoud Khabiri; Amin Mortaheb; Saeid Hoseini (Wolters Kluwer Medknow Publications, 2022)
Background: This study assessed the effect of sodium hypochlorite on cyclic fatigue resistance of RaCe, HyFlex CM and XP-endo Shaper files. Materials and Methods: In this in vitro, experimental study, 90 RaCe, HyFlex CM and XP-endo Shaper files (n = 30 of each) were divided into two groups (n = 45). Group 1 included 15 files of each rotary system, which were immersed in 37°C sodium hypochlorite (5.25%) for 5 min. Group 2 files were immersed in 37°C saline for 5 min. The files underwent cyclic fatigue testing using simulated root canals in which, the rotary files could freely rotate until fracture. Time of fracture was recorded by a chronometer and the number of cycles until fracture was calculated. Data were analyzed using two-way ANOVA and Bonferroni test (α = 0.05). Results: No significant difference existed in the mean number of cycles or rotation time of files between saline and sodium hypochlorite (P > 0.05). The mean rotation time of RaCe was significantly shorter than that of HyFlex and XP-endo Shaper in both solutions (P < 0.05). The mean number of cycles of RaCe was significantly lower than that of HyFlex and XP-endo Shaper files in both solutions (P < 0.05). The mean number of cycles of HyFlex was significantly lower than that of XP-endo Shaper (P < 0.05). >Conclusion: Immersion of rotary files made of different alloys in 5.25% sodium hypochlorite for 5 min had no effect on their fracture resistance. However, type of file alloy affected its fatigue resistance such that XP-endo Shaper showed the highest and RaCe showed the lowest fatigue resistance.